PERAN INOVASI PRODUK MEMEDIASI ORIENTASI PELANGGAN TERHADAP KINERJA PEMASARAN - Allen Ken Alexandro; Lie Heng (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of customer orientation on marketing performance with product innovation as a mediating variable in aluminum craft MSMEs. This study is an associative quantitative research that aims to examine the relationship between product innovation and customer orientation on marketing performance, as well as to test the mediating role of marketing performance. Data were collected through questionnaires and interviews with aluminum-based handicraft SMEs in Pontianak and Kubu Raya. The population consisted of all SMEs in this sector, with a sample of 110 business actors determined using purposive sampling based on the criterion of having operated for at least three years. Data analysis was conducted using SEM with the aid of AMOS software. The results show that three of the four hypotheses tested are significant, namely (1) customer orientation has a direct effect on product innovation, (2) product innovation has a positive effect on marketing performance, and (3) customer orientation does not have a direct effect on marketing performance.